Authoritarianism, Democracy, Islamic Movements and Contestations of Islamic Religious Ideas in Indonesia - Barton, Greg (Religions, 2021)
Since independence, Islamic civil society groups and intellectuals have played a vital role in Indonesian politics. This paper seeks to chart the contestation of Islamic religious ideas in Indonesian politics and society throughout the 20th Century, from the declaration of independence in 1945 up until 2001. This paper discusses the social and political influence of, and relationships between, three major Indonesian Islamic intellectual streams: Modernists, Traditionalists, and neo-Modernists. It describes the intellectual roots of each of these Islamic movements, their relationships with the civil Islamic groups Muhammadiyah and Nahdlatul Ulama (NU), their influence upon Indonesian politics, and their interactions with the state. The paper examines the ways in which mainstream Islamic politics in Indonesia, the world’s largest majority Muslim nation, has been shaped by disagreements between modernists and traditionalists, beginning in the early 1950s. Disagreements resulted in a schism within Masyumi, the dominant Islamic party, that saw the traditionalists affiliated with NU leave to establish a separate NU party. Not only did this prevent Masyumi from coming close to garnering a majority of the votes in the 1955 election, but it also contributed to Masyumi veering into Islamism. This conservative turn coincided with elite contestation to define Indonesia as an Islamic state and was a factor in the party antagonizing President Sukarno to the point that he moved to ban it. The banning of Masyumi came as Sukarno imposed ‘guided democracy’ as a soft-authoritarian alternative to democracy and set in train dynamics that facilitated the emergence of military-backed authoritarianism under Suharto. During the four decades in which democracy was suppressed in Indonesia, Muhammadiyah and Nahdlatul Ulama, and associated NGOs, activists, and intellectuals were the backbones of civil society. They provided critical support for the non-sectarian principles at the heart of the Indonesian constitution, known as Pancasila. This found the strongest and clearest articulation in the neo-Modernist movement that emerged in the 1980s and synthesized key elements of traditionalist Islamic scholarship and Modernist reformism. Neo-Modernism, which was articulated by leading Islamic intellectual Nurcholish Madjid and Nahdlatul Ulama Chairman Abdurrahman Wahid, presents an open, inclusive, progressive understanding of Islam that is affirming of social pluralism, comfortable with modernity, and stresses the need for tolerance and harmony in inter-communal relations. Its articulation by Wahid, who later became president of Indonesia, contributed to Indonesia’s transition from authoritarianism to democracy. The vital contribution of neo-Modernist Islam to democracy and reform in Indonesia serves to refute the notion that Islam is incompatible with democracy and pluralism.